Cost-Effectiveness of Rheumatic Heart Disease Echocardiographic Screening in Brazil: Data from the PROVAR+ Study: Cost-effectiveness of RHD screening in Brazil - Jasper Ubels; Craig Sable; Andrea Z. Beaton; Maria Carmo P. Nunes; Kaciane K. B. Oliveira; Lara C. Castro; Isabella M. Teixeira; Gabriela Z. L. Ruiz; Letícia Maria M. Rabelo; Alison R. Tompsett; Antonio Luiz P. Ribeiro; Klas-Göran Sahlen; et al. (Ubiquity Press, 2020)
Introduction: In recent years, new technologies - noticeably ultra-portable echocardiographic machines - have emerged, allowing for Rheumatic Heart Disease (RHD) early diagnosis. We aimed to perform a cost-utility analysis to assess the cost-effectiveness of RHD screening with handheld devices in the Brazilian context. Methods: A Markov model was created to assess the cost-effectiveness of one-time screening for RHD in a hypothetical cohort of 11-year-old socioeconomically disadvantaged children, comparing the intervention to standard care using a public perspective and a 30-year time horizon. The model consisted of 13 states: No RHD, Undiagnosed Asymptomatic Borderline RHD, Diagnosed Asymptomatic Borderline RHD, Untreated Asymptomatic Definite RHD, Treated Asymptomatic Definite RHD, Untreated Mild Clinical RHD, Treated Mild Clinical RHD, Untreated Severe Clinical RHD, Treated Severe Clinical RHD, Surgery, Post-Surgery and Death. The initial distribution of the population over the different states was derived from primary echo screening data. Costs of the different states were derived from the Brazilian public health system database. Transition probabilities and utilities were derived from published studies. A discount rate of 3%/year was used. A cost-effectiveness threshold of $25,949.85 per Disability Adjusted Life Year (DALY) averted is used in concordance with the 3x GDP per capita threshold in 2015. Results: RHD echo screening is cost-effective with an Incremental Cost-Effectiveness Ratio of $10,148.38 per DALY averted. Probabilistic modelling shows that the intervention could be considered cost-effective in 70% of the iterations. Conclusion: Screening for RHD with hand held echocardiographic machines in 11-year-old children in the target population is cost-effective in the Brazilian context. Highlights: A cost-effectiveness analysis showed that Rheumatic Heart Disease (RHD) echocardiographic screening utilizing handheld devices, performed by non-physicians with remote interpretation by telemedicine is cost-effective in a 30-year time horizon in Brazil. The model included primary data from the first large-scale RHD screening program in Brazilian underserved populations and costs from the Unified Health System (SUS), and suggests that the Incremental Cost-Effectiveness Ratio of the intervention is considerably below the acceptable threshold for Brazil, even after a detailed sensitivity analysis. Considering the high prevalence of subclinical RHD in Brazil, and the significant economic burden posed by advanced disease, these data are important for the formulation of public policies and surveillance approaches. Cost-saving strategies first implemented in Brazil by the PROVAR study, such as taskshifting to non-physicians, computer-based training, routine use of affordable devices and telemedicine for remote diagnosis may help planning RHD control programs in endemic areas worldwide.